2019
DOI: 10.3390/ijms20153692
|View full text |Cite
|
Sign up to set email alerts
|

Affinities of Terminal Inverted Repeats to DNA Binding Domain of Transposase Affect the Transposition Activity of Bamboo Ppmar2 Mariner-Like Element

Abstract: Mariner-like elements (MLE) are a super-family of DNA transposons widespread in animal and plant genomes. Based on their transposition characteristics, such as random insertions and high-frequency heterogeneous transpositions, several MLEs have been developed to be used as tools in gene tagging and gene therapy. Two active MLEs, Ppmar1 and Ppmar2, have previously been identified in moso bamboo (Phyllostachys edulis). Both of these have a preferential insertion affinity to AT-rich region and their insertion sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Insufficiency of enzymes encoded by TEs may explain the insufficient quantity for the transposition process. For instance, transposition of Ppmar1 and Ppmar2 (Mariner-like elements (MLEs) isolated from Moso bamboo) is determined by the quantity of transposases present inside the nucleus [156,157]. This suggests that MLEs generally have the potential to develop a self-regulatory strategy that can control their amplification and copy numbers by minimization of transposases.…”
Section: Balance Between Te Expression and Repressionmentioning
confidence: 99%
“…Insufficiency of enzymes encoded by TEs may explain the insufficient quantity for the transposition process. For instance, transposition of Ppmar1 and Ppmar2 (Mariner-like elements (MLEs) isolated from Moso bamboo) is determined by the quantity of transposases present inside the nucleus [156,157]. This suggests that MLEs generally have the potential to develop a self-regulatory strategy that can control their amplification and copy numbers by minimization of transposases.…”
Section: Balance Between Te Expression and Repressionmentioning
confidence: 99%
“…Additionally, they identified transposon variations that depict adaptive responses during the evolutionary process of moso bamboo. Subsequently, through functional analyses of transposons, Ramakrishnan, Zhou, Pan, Hänninen, Yrjälä, et al (2019), Ramakrishnan, Zhou, Pan, Hänninen, Tang, et al (2019) identified activities of mariner‐like elements ( MLE ) of the moso bamboo, drawing evolutionary connotations.…”
Section: Role Of Next‐generation Sequencing Approaches In Expediting mentioning
confidence: 99%
“…Previous studies attempted to understand the transposition control of MLEs . Ramakrishnan, Zhou, Pan, Hänninen, Yrjälä, et al (2019) were able to alter the transposition frequency of Ppmar2 by 1.5–2.0 times more than that of the wild‐type yeast by increasing the affinities of terminal inverted repeats (TIRs) toward the DNA‐binding domain of TPase. Further, the nuclear export signal (NES) domains of both Ppmar1 and Ppmar2 elements regulate the nuclear export of TPases that ultimately influences the transposition activity of MLEs (Ramakrishnan, Zhou, Pan, Hänninen, Tang, et al, 2019).…”
Section: Prospects For Genomics‐assisted Breedingmentioning
confidence: 99%
“…Two full-length MLEs named Ppmar1 and Ppmar2 were previously identified from the genome of moso bamboo (Phyllostachys edulis) (Zhou et al, 2015). Ppmar1 and Ppmar2 were shown to be transposable in Arabidopsis thaliana and yeast (Zhou et al, 2016;Zhou et al, 2017;Ramakrishnan et al, 2019a;Ramakrishnan et al, 2019b). Site-directed mutation boosted the activity of the Ppmar1 mutant (S171A) by more than 10-fold (Zhou et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…expression vector, pAG415gal-ccdB, as described by Ramakrishnan et al (2019a;2019b). Ppmar2 non-autonomous transposon (Ppmar2NA) was cloned by amplifying its 5' and 3' TIRs as well as the adjacent sequence, followed by an overlap PCR.…”
Section: Introductionmentioning
confidence: 99%